A case report of multi-ligaments injury of the ACL-MCL-PT combined with an occult fracture of the posterolateral tibial plateau. (June 2021) - Xie, Tao; Han, Xiao; Zhou, Shao-bo; Zhu, Liu-long; He, Qi-fang
Abstract: The anterior cruciate ligament and medial collateral ligament are important static stabilizers of the knee. The patellar tendon is part of the knee extensor mechanism. The injury simultaneously involving these three structures is very rare. This paper reports a case with simultaneous ipsilateral rupture of the anterior cruciate ligament, medial collateral ligament, patellar tendon, and an occult compression fracture of the posterolateral tibial plateau. This injury pattern has not been reported in literature yet. The injury mechanism was hypothesized as a sudden anterior translation and valgus of the proximal tibia when the knee was in high flexion, followed by an eccentric quadriceps' contracture. In the followed management, ruptured medial collateral ligament and patellar tendon were sutured with augment, while the torn anterior cruciate ligament and fracture were treated conservatively. The outcome of the treatment was satisfactory, and no complication was observed. To this combined injury, a comprehensive consideration, including physical examination, multiple imaging examinations, and analysis of injury mechanism, is essential for a full diagnosis and treatment decision. Especially, computed tomography may help to identify an occult or non-displaced fracture, which would be easily misdiagnosed when nothing unusual was found in routine X-rays. In the treatment, it is suggested to perform a selective or step-by-step repair to the damaged structures, rather than an immediate total repair after injury.